2015
DOI: 10.1158/0008-5472.can-14-1053
|View full text |Cite
|
Sign up to set email alerts
|

Host Age Is a Systemic Regulator of Gene Expression Impacting Cancer Progression

Abstract: Aging is the major determinant of cancer incidence, which, in turn, is likely dictated in large part by processes that influence the progression of early subclinical (occult) cancers. However, there is little understanding of how aging informs changes in aggregate host signaling that favor cancer progression. In this study, we provide direct evidence that aging can serve as an organizing axis to define cancer progression-modulating processes. As a model system to explore this concept, we employed adolescent (6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 49 publications
4
53
1
Order By: Relevance
“…This miRNA signature consists of 10 miRNAs: miR-130, miR-27, miR-17, miR-10, miR-155, let-7a-5p, let-7, miR-24-3p, miR-15, and miR-16-5p. We previously reported that during tumor progression (and possibly tumor initiation), there is a systemic impact on the host influencing tumor dynamics and molecular factors originating from the host that may be the true “drivers” for carcinogenesis [37, 38]. These data begin to reveal universal drivers (i.e., miRNAs) in the host responsible for DLBCL formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This miRNA signature consists of 10 miRNAs: miR-130, miR-27, miR-17, miR-10, miR-155, let-7a-5p, let-7, miR-24-3p, miR-15, and miR-16-5p. We previously reported that during tumor progression (and possibly tumor initiation), there is a systemic impact on the host influencing tumor dynamics and molecular factors originating from the host that may be the true “drivers” for carcinogenesis [37, 38]. These data begin to reveal universal drivers (i.e., miRNAs) in the host responsible for DLBCL formation.…”
Section: Resultsmentioning
confidence: 99%
“…To examine this theory, we collected peripheral blood from 3.5 months old (“ young” ) and 15 months old (“ old” ) Smurf2 T/T and wild-type mice. These ages are roughly equivalent to a 20-year old human for young mice and 50-year old human for the old mice [37]. At the time the serum was prepared none of the old mice had any noticeable tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Data for the L428 cell line (part of a larger dataset which was not used in this manuscript) was corrected through normalization of the housekeeping genes, quantile normalized, and then statistically relevant genes were determined with one-way ANOVA analysis with FDR <0.05. Details on the pathway analysis, networks, and the unbiased method to determine the key significant genes are previously published in (23, 26, 27). …”
Section: Methodsmentioning
confidence: 99%
“…No convincing animal models were found in the literature to demonstrate a consistent effect of age on tumor progression or gene expression, and different cell lines exhibit heterogeneous effects when studying the aging host. Anti‐tumor immune response and transforming growth factor beta function are attenuated in aging hosts, but these would be expected to encourage more rapid growth . Neo‐angiogenesis may be impaired in the aging host and thereby diminish the robustness of metastases outgrowth .…”
Section: Are Tumors More Indolent In the Aged?mentioning
confidence: 99%
“…Anti-tumor immune response and transforming growth factor beta function are attenuated in aging hosts, but these would be expected to encourage more rapid growth. 8,9 Neo-angiogenesis may be impaired in the aging host and thereby diminish the robustness of metastases outgrowth. 10,11 Hence, there is no convincing biologic evidence that the breast cancer aggressiveness decreases with the age.…”
Section: Aged?mentioning
confidence: 99%